PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, BUDAYA PERUSAHAAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI PT. PLN (PERSERO) WILAYAH PADANG SUMATERA BARAT - Mirza, Bani; Lukito, Hendra (Sekolah Tinggi Ilmu Ekonomi Semarang, 2018)
This research aims to determine and analyze the influence of transformational leadership, corporate culture, and work motivation on employee performance at PT. PLN (Persero) Region of West Sumatra Area Padang. This research is exploratory research with quantitative method. The sampling technique was conducted by the census method, with the sample number of 100 employees. This research uses Partial Least Squares-Structural Equations Modeling (PLS-SEM) with smartPLS 3 program. The results show that transformational leadership have positive but not significant effect to employee performance, Corporate culture have positive and significant effect to employee performance, and work motivation have negative but not significant effect to employee performance at PT. PLN (Persero) Region of West Sumatra Area Padang.